Could Vegans and Lycra Cyclists be Bad for the Planet? Theorizing the Role of Moralized Minority Practice Identities in Processes of Societal‐Level Change. (25th December 2019) - Kurz, Tim; Prosser, Annayah M.B.; Rabinovich, Anna; O'Neill, Saffron
Abstract: Shifting society to more sustainable modes of consumption poses significant challenges to the way people live their lives. Many everyday practices commensurate with addressing sustainability goals are currently minority pursuits, especially in highly industrialized countries. Such minority practices often come to form the basis of social identities (e.g., as "vegans" or "cyclists"). These moralized minority practice identities (MMPIs) represent the focus of this theoretical article. We theorize the nature and genesis of MMPIs, discuss how their characteristics shape intergroup interactions, and consider implications for societal‐level change. We make the contentious suggestion that, contrary to what might be predicted on the basis of social identity approaches to social change, strong identification with "green practice" groups may hamper, rather than facilitate, societal‐level shifts toward sustainability. We discuss the need for policy approaches that enable people to experiment with new sustainable practices without the pressure to commit to a particular practice identity.